Obesity and HIV: a compounding problem. Issue 4 (2nd October 2018) - Biggs, Chara; Spooner, Elizabeth
Abstract: Objectives: A cross-sectional study was undertaken at Lancers Road Clinic, Durban, South Africa to determine body composition, haemoglobin, serum albumin and serum high sensitivity C-reactive protein (hs-CRP) levels in asymptomatic ART-naive HIV positive adults. Methods: All eligible adults attending the clinic were sampled. Body composition was assessed using deuterium dilution. Descriptive statistics, Wilcoxon rank-sum test, chi-square test, Fisher's exact test and Spearman's rank correlation coefficient were used for data analysis. Results: A total of 84 participants (CD4 count: 542.5 ± 145 cell/mm 3 ) enrolled. The mean body mass index (BMI) was 29.5 (± 6.4) kg/m 2 and the mean fat mass percentage was 44.9 (± 18.7). The prevalence of overweight (26.2%, 22/84) and obesity (46.4%, 39/84) was high. Mean haemoglobin (Hb) levels were 12.0 ± 1.6 g/dl. Mild, moderate and severe anaemia was present in 21.4% (18/84), 20.2% (17/84) and 1.2% (1/84) of patients, respectively. Mean albumin levels (36.2 ± 3.8 g/l) were on the borderline low range of normal with mildly depleted albumin levels being present in a third (32.1%, 27/84) of patients. The mean hs-CRP levels (5.5 ± 7.2 mg/l) were high. Conclusion: In this cohort of patients, wasting was not associated with HIV as the prevalence of overweight/obesity was high and followed the population trend in SA. This seemingly well, asymptomatic population of people living with HIV was at an increased risk of morbidity, progression and death due to the compounding factors of overweight/obesity, hypoalbuminemia, raised hs-CRP levels and anaemia.